Negotiation Patterns in Inter-Organizational Religious Marriages and Their Implications for Social Harmony in Ponorogo - Bagus Ahmad Setyo Binangkit; Miftahul Huda; Lukman Santoso (Institut Agama Islam Negeri Ponorogo, 2026)
Background/Introduction: Inter-organizational Islamic marriages in Ponorogo represent a significant social phenomenon due to strong affiliations with religious organizations such as Nahdlatul Ulama, Muhammadiyah, Jamaah Tabligh, Majelis Tafsir Al-Qur’an, and Lembaga Dakwah Islam Indonesia. Differences in practices and values require negotiation to maintain harmony. Research Objectives: This study aims to analyze negotiation patterns, identify factors influencing success or failure, and examine social implications of inter-organizational marriages. Methodology: This research uses a qualitative field approach through observation, in-depth interviews, and documentation involving six couples and religious leaders. Data were analyzed using inductive and deductive methods within Islamic law and negotiation theory frameworks.Results: Negotiation processes emphasize communication, mutual understanding, and compromise through family discussions and occasional involvement of religious leaders. Success factors include family support, openness, adaptability, shared religious commitment, and mutual respect. Challenges arise from differences in religious understanding, social pressure, and cultural background. Unique Contribution: This study highlights the role of Islamic values, tolerance, and social actors in shaping flexible and harmonious negotiation patterns in inter-organizational marriages. Conclusion: Effective negotiation strengthens marital harmony and promotes social cohesion within the community. Recommendations: Strengthening tolerance literacy, improving family communication, and involving religious leaders constructively are essential to support harmonious inter-organizational marriages.